Addition of a pontic to all-ceramic Turkom-Cera fixed partial denture restorations - Uludag, Bulent (Medknow Publications & Media Pvt Ltd, 2013)
High-strength all-ceramic materials are commonly used in dentistry. When complications occur in an all-ceramic restoration, the restoration is usually replaced. This article describes the time-saving ability and cost-effectiveness of this novel technique for the addition of a pontic in two complicated clinical cases. Turkom-Cera(™) [Turkom-Ceramic (M) Sdn. Bhd.] with aluminum oxide (99.98%) is an all-ceramic system that offers the option of addition of a new pontic to the sintered framework. The new pontic was cut off from an alumina blank [Turkom-Ceramic (M) Sdn. Bhd.], moistened, and attached to the framework using alumina gel [Turkom-Ceramic (M) Sdn. Bhd.]. The framework was veneered with veneering porcelain (Vita VM 7; VITA Zahnfabrik). The two cases presented here involving the addition of a pontic to sintered framework were followed up for at least 1 year. No complication was detected or reported by the patients. Alumina- and zirconia-based ceramics are particularly suitable for for all-ceramic restorations in high-stress bearing areas. However, replacement of a failed all-ceramic restoration is not the most practical solution, considering both cost and tooth-related factors. This attractive feature of the Turkom-Cera allows the repair of a fractured ceramic coping or the addition of a new pontic to restorations.